Bradykinin receptor in immune-mediated renal tubular injury in trichloroethylene-sensitized mice: Impact on NF-κB signaling pathway. (1st January 2018) - Yang, Ling; Zhang, Jiaxiang; Li, Na; Xie, Haibo; Chen, Shuangping; Wang, Hui; Shen, Tong; Zhu, Qi-xing
Abstract: Trichloroethylene (TCE) is known to induce skin disorders and multi-system dysfunction, but the mechanism of this multi-organ injury is not entirely clear. It was shown in a previous study that levels of pivotal end-products of the kallikrein-kinin system (KKS), i.e. bradykinin (BK) and BK receptors B1R/B2R, in the kidneys were increased by TCE exposure. Unfortunately, how BK and its receptors acted in the etiology of the induced renal injury is not clear. Thus, this study explored any correlation between BK receptors and immune renal injury in TCE-sensitized mice by blocking the BK receptors B1R/B2R. BALB/c mice were sensitized (via skin) by TCE, with or without pre-treatment with a B1R or B2R antagonist. Renal lesions, increased expressions of B1R, B2R, Kim-1, Lipocalin-2, and NF-κB p65 subunit on tubular epithelial cells were all observed in TCE-sensitized mice. Serum levels of creatinine (Cr), microglobulin α1 and β2, along with mRNA levels for inflammatory cytokines and NF- κB p65 in kidneys, were all increased by 72 h after a final challenge. Highly selective antagonist pre-treatment blocked B2R and significantly attenuated TCE-induced changes. Blocking B1R or B2R attenuated release of pro-inflammatory cytokines and activation of NF-κB signaling pathway (as reflected in lower up-regulation of pIκB and nuclear NF-κB p65 subunit, and down-regulation of IκB in the kidneys. These results provided evidence that TCE-sensitization caused KKS activation and enhanced the expression of B1R and B2R on tubular epithelial cells. This, in turn, accelerated NF-κB signaling pathway activation and amplified inflammatory cytokine release, which all likely contributed to TCE-induced immune renal injury.